Army support of military cyberspace operations : joint contexts and global escalation implications - Caton, Jeffrey L.; Army War College (U.S.). Strategic Studies Institute; Army War College (U.S.). Press (Carlisle, PA : Strategic Studies Institute and U.S. Army War College Press, 2015)
"Military cyberspace operations have evolved significantly over the past 2 decades and are now emerging into the realm of military operations in the traditional domains of land, sea, and air. The goal of this monograph is to provide senior policymakers, decisionmakers, military leaders, and their respective staffs with a better understanding of Army cyberspace operations within the context of overall U.S. military cyberspace operations. It examines the development of such operations in three major sections. First, it looks at the evolution of Department of Defense cyberspace operations over the past decade to include the founding of U.S. Cyber Command from its roots in various military units focused on defensive and offensive cyberspace operations. Second, it examines the evolution of the Army implementation of cyberspace operations toward the initial establishment of Army Cyber Command as well as recent efforts to establish Fort Gordon, Georgia as the center of gravity for Army cyberspace activities. Third, it explores the role of cyberspace operations in the escalation of international conflict, focusing on the sufficiency of the current cyberspace force structure to address an international environment of multiple actors interacting with varying degrees of tension"--Publisher's web site.
Evolution of military cyberspace operations -- Evolution of Army cyberspace operations -- Cyberspace operations in a global context -- Recommendations -- Concluding remarks.
"January 2015."
Format not distributed to depository libraries.
Includes bibliographical references.
Also available online in PDF format from Strategic Studies Institute (SSI) web site.
Keywords: United States. -- Strategic Command (2002- ). -- Cyber Command; Cyberspace operations (Military science) -- United States; Unified operations (Military science)